Podoplanin: A potential therapeutic target for thrombotic diseases - Huang, Yaqian; Lu, Manli; Wang, Yi; Zhang, Chunyuan; Cao, Yongjun; Zhang, Xia (Frontiers in Neurology, 2023)
As a specific lymphatic marker and a key ligand of C-type lectin-like receptor 2 (CLEC-2), podoplanin (Pdpn) is involved in various physiological and pathological processes such as growth and development, respiration, blood coagulation, lymphangiogenesis, angiogenesis, and inflammation. Thrombotic diseases constitute a major cause of disability and mortality in adults, in which thrombosis and inflammation play a crucial role. Recently, increasing evidence demonstrates the distribution and function of this glycoprotein in thrombotic diseases such as atherosclerosis, ischemic stroke, venous thrombosis, ischemic-reperfusion injury (IRI) of kidney and liver, and myocardial infarction. Evidence showed that after ischemia, Pdpn can be acquired over time by a heterogeneous cell population, which may not express Pdpn in normal conditions. In this review, the research progresses in understanding the roles and mechanisms of podoplanin in thromobotic diseases are summarized. The challenges of podoplanin-targeted approaches for disease prognosis and preventions are also discussed.